Understanding Entitativity: Are There Real Differences between Approaches? - Елена Рафиковна Агадуллина; Андрей Владимирович Ловаков (Psychology. Journal of the Higher School of Economics, 2018)
Entitativity is a key construct for understanding group perception. But the question of understanding this construct is troublesome. There are three theoretical approaches to understanding group entitativity (essence-based entitativity, agency-based entitativity and unity-based entitativity) and at least two different empirical strategies for measuring the entitativity (operationalization in one of the theoretical approaches and entitativity as a set of characteristics from different approaches that work as a common scale). This paper aims to answer the question whether there are any differences in the various understanding of entitativity. In our studies entitativity is described as involving three components: “essence” (the group members’ similarity), “agency” (the goals and the interaction between group members) and “unity” (the cohesion of a group and the degree of the group importance). In Study 1 a series of confirmatory factor analyses revealed that the three-component model of entitativity fitted the data well for different groups (ingroup, outgroup, intimacy groups and social categories) and demonstrated a better fit compared to the alternative model (entitativity as a common construct). The results of the study suggest that the components of entitativity are interrelated, but not identical to each other. Study 2 demonstrated that the use of different ways of understanding entitativity (such as “essence”, “agency”, and “unity” components or the common entitativity scale) doesn’t lead to differences related to blatant prejudice, subtle prejudice, and identification. Our results demonstrate that there are no substantial differences between the measurements of entitativity. The implications of the obtained results for future research are discussed.